Assessing the influence of biogeographical region and phylogenetic history on chemical defences and herbivory in Quercus species. (September 2018) - Moreira, Xoaquín; Abdala-Roberts, Luis; Galmán, Andrea; Francisco, Marta; Fuente, María de la; Butrón, Ana; Rasmann, Sergio
Abstract: Biogeographical factors and phylogenetic history are key determinants of inter-specific variation in plant defences. However, few studies have conducted broad-scale geographical comparisons of plant defences while controlling for phylogenetic relationships, and, in doing so, none have separated constitutive from induced defences. This gap has limited our understanding of how historical or large-scale processes mediate biogeographical patterns in plant defences since these may be contingent upon shared evolutionary history and phylogenetic constraints. We conducted a phylogenetically-controlled experiment testing for differences in constitutive leaf chemical defences and their inducibility between Palearctic and Nearctic oak species ( Quercus, total 18 species). We induced defences in one-year old plants by inflicting damage by gypsy moth larvae ( Lymantria dispar ), estimated the amount of leaf area consumed, and quantified various groups of phenolic compounds. There was no detectable phylogenetic signal for constitutive or induced levels of most defensive traits except for constitutive condensed tannins, as well as no phylogenetic signal in leaf herbivory. We did, however, find marked differences in defence levels between oak species from each region: Palearctic species had higher levels of constitutive condensed tannins, but less constitutive lignins and less constitutive and induced hydrolysable tannins compared with Nearctic species. Additionally, Palearctic species had lower levels of leaf damage compared with Nearctic species. These differences in leaf damage, lignins and hydrolysable (but not condensed) tannins were lost after accounting for phylogeny, suggesting that geographical structuring of phylogenetic relationships mediated biogeographical differences in defences and herbivore resistance. Together, these findings suggest that historical processes and large-scale drivers have shaped differences in allocation to constitutive defences (and in turn resistance) between Palearctic and Nearctic oaks. Moreover, although evidence of phylogenetic conservatism in the studied traits is rather weak, shared evolutionary history appears to mediate some of these biogeographical patterns in allocation to chemical defences. Graphical abstract: There was a marked difference in constitutive levels of leaf chemical defences between Nearctic and Palearctic Quercus species, particularly lignins, condensed tannins, and hydrolysable tannins, but no difference between biogeographical regions in the inducibility of most these compounds (except hydrolysable tannins). Highlights: There was no detectable phylogenetic signal for most of the defensive chemical traits studied . Palearctic (vs. Nearctic) species invested more in constitutive condensed tannins but less in lignins and hydrolysable tannins. There was no difference between biogeographical regions in the inducibility of most chemical defences. Palearctic oak species exhibited a lower mean level of leaf herbivore damage compared to Nearctic oak species.